Fiscal Indicators for Economic Growth : Illusory Search? (IMF Working Papers; Working Paper ;, 1990)
The search for ways to ensure growth while accommodating necessary expenditure cuts to correct fiscal imbalances, has often led to the advocacy of the government own savings (GOS) measure as an indicator of growth potential in fiscal adjustment. This paper critically examines the rationale of this approach and its implicit assumption of the primacy of capital expenditure for the growth process. In light of the problems revealed in the GOS approach, the paper explores the possibility of alternative weighted expenditure indicators and illustrates the proposed technique, employing data from Thailand.